A comparative study using water atomized and gas atomized powder in laser powder bed fusion – Assessment of the fatigue performance. (March 2023) - Richter, Julia; Torrent, Christof Johannes Jaime; Krochmal, Marcel; Wegener, Thomas; Vollmer, Malte; Niendorf, Thomas
Highlights: Water and gas atomized powder were applied in PBF-LB/M process obtaining a relative density of 99.9 % irrespective of the initial powder. Under tensile deformation, the Fe specimens built by PBF-LB/M using both powders are characterized by high strength and ductility being superior to conventional processed material. Based on analysis of fatigue life, it could be revealed that the specimens built using water atomized powder are competitive to gas atomized. The utilization of spattered powders in PBF-LB/M process is thought to be robustly feasible. Abstract: Gas-atomized (GA, spherical) and water-atomized (WA, spattered) commercially pure iron (cp-Fe) powders were processed using laser-based powder bed fusion, resulting in a slightly higher porosity of the WA condition. In addition to characterization of quasi-static mechanical properties, fatigue tests, which are known to be detrimentally affected by porosity, were finally considered, revealing good properties even for the WA condition. In terms of microstructure stability, the GA and WA specimens significantly differ; effects seen can be rationalized based on the actual chemical compositions. While the GA specimens show an obvious yield phenomenon and softening under cyclic loading, the WA specimens reveal microstructure stability in cyclic tests.